Characterization of Fruit Quality Attributes and Cell Wall Metabolism in 1-Methylcyclopropene (1-MCP)-Treated ‘Summer King’ and ‘Green Ball’ Apples During Cold Storage - Win, Nay Myo; Yoo, Jingi; Kwon, Soon-Il; Watkins, Christopher B.; Kang, In-Kyu (Frontiers in Plant Science, 2019)
This study aimed to elucidate whether 1-methylcyclopropene (1-MCP) treatment delays the fruit softening mechanism associated with fruit quality of the newly released apple cultivars ‘Summer King’ and ‘Green Ball’ during cold storage. For both cultivars, the fruit treated with 1-MCP exhibited lower internal ethylene concentration, higher firmness, and higher titratable acidity over the control fruit, in association with less fruit softening. In addition, the treated fruit significantly delayed fresh weight loss and reduction of soluble solids content, especially in ‘Green Ball’. Moreover, slower degradation of cell wall components (water-soluble pectin, sodium carbonate-soluble pectin, hemicellulose, and cellulose) was also observed in the treated fruit in comparison to the control fruit. Similarly, the enzymatic activities (of polygalacturonase, pectin methylesterase, cellulase, β-galactosidase, and α-L-arabinofuranosidase) that cause cell wall degradation were relatively lower in the treated fruit than the control fruit for both cultivars, which was further proved by transcriptional analysis of the genes encoding the enzymes. Overall, the results suggested that the exploitation of 1-MCP is useful to delay the fruit softening mechanism of the two cultivars during cold storage, especially by delaying the degradation of cell wall components and enzymatic activities of cell wall hydrolysis.